2021
DOI: 10.3390/plants10102164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fire Frequency on the Flammability of Two Mediterranean Pines: Link with Needle Terpene Content

Abstract: Flammability is a major factor involved in Mediterranean plant evolution that has led to the diversity of fire-related traits according to fire regimes and fire-adaptive strategies. With on-going climate change, new fire regimes are threatening plant species if they do not adapt or acclimate. Studying flammability and terpene content variation according to the different fire frequencies in the recent fire history represents a great challenge to anticipating the flammability of ecosystems in the near future. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…This observation deserves focused examination in the future. Additional variability apart from that described in both ordinations can be explained by parameters that are not represented in the generated matrices, including genotype ( Rubini et al., 2022 ), pests ( Gaspar et al., 2020 ; Gonçalves et al., 2020 ; Kopaczyk et al., 2020 ; López-Goldar et al., 2020 ), and proximity of forest fires ( Cannac et al., 2009 ; Romero and Ganteaume, 2021 ), as suggested before. The impact of silvicultural conditions on resin composition, e.g., the resin tapping method, cannot be overlooked as well ( Rubini et al., 2022 ).…”
Section: Discussionmentioning
confidence: 89%
“…This observation deserves focused examination in the future. Additional variability apart from that described in both ordinations can be explained by parameters that are not represented in the generated matrices, including genotype ( Rubini et al., 2022 ), pests ( Gaspar et al., 2020 ; Gonçalves et al., 2020 ; Kopaczyk et al., 2020 ; López-Goldar et al., 2020 ), and proximity of forest fires ( Cannac et al., 2009 ; Romero and Ganteaume, 2021 ), as suggested before. The impact of silvicultural conditions on resin composition, e.g., the resin tapping method, cannot be overlooked as well ( Rubini et al., 2022 ).…”
Section: Discussionmentioning
confidence: 89%
“…Canopy depth and leaf area index are forest stand characteristics negatively correlated with ignitability, while clearcuts of former Scots pine stands showed the highest ignition probability; also the frequency of ignitions was lower for sites with higher canopy cover and leaf area index (Tanskanen, 2007). The flammability of pine stands was shown to be higher in stands that have burned previously considering flame height and residence, shoot flammability as well as time to ignition or higher combustibility (Romero and Ganteaume, 2021).…”
Section: Introductionmentioning
confidence: 92%
“…We suggest that a candidate trait is the presence of volatile organic compounds (VOCs) such as terpenoids, particularly in species within the family Myrtaceae, a family well known for its VOCs (Whiffin and Ladiges 1992;Keszei et al 2008). Previous work has identified links between flammability and VOCs (Pausas et al 2016;Romero and Ganteaume 2021). Indeed, Della Rocca et al (2017) suggested that terpenoids should be included in physical models of the prediction and propagation of wildfire in mediterranean vegetation given their strong influence on plant flammability.…”
Section: Trait Relationships With Shoot Flammabilitymentioning
confidence: 99%